EVALUATION OF 18FLUORINFLUOROTHYMIDINE UPTAKE IN BREAST AND LUNG-TUMOR BEARING MICE - Nguyen , Thi Kim Dung; Mai , Hong Son; Nguyen, Khac That; Le, Ngoc Ha; Pham , Dang Tung; Nguyen , Quoc Thang (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2021)
Background: PET (positron emission tomography) techniques and radiopharmaceutical tracers are becoming increasingly common in clinical practice. Since 1991, 3’-deoxy-3’-18Fluorine-Fluorothymidine (18F-FLT) has been studied as a PET tracer for tumor proliferation assessment. The purpose of this study was to assess tracer uptake (%ID/g) in tumor-bearing mice and the relationship between uptake values and Ki-67 expression. Materials and methods: two cell lines including breast cancer cell line 4T1 and lung cancer cell line LLC were inoculated into BALB/c mice. The radiotracer was then injected, and tumor resection was performed 20, 40, 60, and 90 minutes later. Gamma-ray spectrometer was used to calculate uptake values. Results: The data show that the tumor’s %ID/g were 5.52 ± 0.23 and 4.66 ± 0.49 for the 4T1 and LLC tumors, respectively, at 90 minutes after injection. The LLC tumors presented a higher Ki-67 index than the 4T1 tumors (90.16 ± 2.93% vs 71.83 ± 3.54%). Conclusion: In our model experiment, accumulation of the tracer in the tumor samples correlates with its malignancy which indicates that 18F-FLT could be a feasible PET tracer.